Antiviral and Immunomodulatory Effects of Pelargonium sidoides DC. Root Extract EPs® 7630 in SARS-CoV-2-Infected Human Lung Cells - Papies, Jan; Emanuel, Jackson; Heinemann, Nicolas; Kulić, Žarko; Schroeder, Simon; Tenner, Beate; Lehner, Martin D.; Seifert, Georg; Müller, Marcel A. (Frontiers in Pharmacology, 2021)
Treatment options for COVID-19 are currently limited. Drugs reducing both viral loads and SARS-CoV-2-induced inflammatory responses would be ideal candidates for COVID-19 therapeutics. Previous in vitro and clinical studies suggest that the proprietary Pelargonium sidoides DC. root extract EPs 7630 has antiviral and immunomodulatory properties, limiting symptom severity and disease duration of infections with several upper respiratory viruses. Here we assessed if EPs 7630 affects SARS-CoV-2 propagation and the innate immune response in the human lung cell line Calu-3. In direct comparison to other highly pathogenic CoV (SARS-CoV, MERS-CoV), SARS-CoV-2 growth was most efficiently inhibited at a non-toxic concentration with an IC50 of 1.61 µg/ml. Particularly, the cellular entry step of SARS-CoV-2 was significantly reduced by EPs 7630 pretreatment (10-100 µg/ml) as shown by spike protein-carrying pseudovirus particles and infectious SARS-CoV-2. Using sequential ultrafiltration, EPs 7630 was separated into fractions containing either prodelphinidins of different oligomerization degrees or small molecule constituents like benzopyranones and purine derivatives. Prodelphinidins with a low oligomerization degree and small molecule constituents were most efficient in inhibiting SARS-CoV-2 entry already at 10 µg/ml and had comparable effects on immune gene regulation as EPs 7630. Downregulation of multiple pro-inflammatory genes (CCL5, IL6, IL1B) was accompanied by upregulation of anti-inflammatory TNFAIP3 at 48 hours post-infection. At high concentrations (100 µg/ml) moderately oligomerized prodelphinidins reduced SARS-CoV-2 propagation most efficiently and exhibited pronounced immune gene modulation. Assessment of cytokine secretion in EPs 7630-treated and SARS-CoV-2-coinfected Calu-3 cells showed that pro-inflammatory cytokines IL-1β and IL-6 were elevated whereas multiple other COVID-19-associated cytokines (IL-8, IL-13, TNF-α), chemokines (CXCL9, CXCL10), and growth factors (PDGF, VEGF-A, CD40L) were significantly reduced by EPs 7630. SARS-CoV-2 entry inhibition and the differential immunomodulatory functions of EPs 7630 against SARS-CoV-2 encourage further in vivo studies.